The impact of religious coping and resilience on psychological well-being among international students in Hungary - Somos, Alexandra (2021)
The purpose of the current study was to examine the relationship between acculturative stress, religious coping, resilience and psychological well-being among 176 international students in Hungary. Extending previous research, we hypothesized that resilience and positive religious coping would act as protective factors against stress and would predict higher levels of psychological well-being. More precisely, resilience and positive coping would moderate (exacerbate) the relation between stress and well-being. However, negative religious coping would contribute to lower levels of psychological well-being. Constructs were measured by the following scales: Acculturative Stress Scale for International Students (ASSIS; Sandhu & Asrabadi, 1994), Brief RCOPE Scale (S-BRCS; Pargament et al., 2011), Connor-Davidson Resilience Scale (CD-RISC; Connor & Davidson, 2003) and Psychological Well-Being scale (PWB; Diener et al., 2009). Results indicate that, as predicted, resilience contributed to higher psychological well-being and negative religious coping negatively correlated with psychological well-being. The relationship between positive religious coping and psychological well-being, however, was not found statistically significant. Moreover, the interaction between positive religious coping and resilience showed a surprising, negative influence on psychological well-being. The implications of these findings are critically discussed and are suggested to contribute to the work of university counsellors, student affairs officers, student organizations, such as Erasmus Student Network through providing a better understanding of acculturative stress and different coping processes among international students.